Accounting Knowledge Behavior, Recording Behavior, and Revenue: The Moderating Role of Cultural Behavior - Situmorang, Dokman Marulitua; Freitas, Jorge Ribeiro; Gumbo, Lilian; Simon, Chosani; Parashakti, Ryani Dhyan (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2024)
The primary aim of this study is to investigate the influence of accounting knowledge and recording practices on the revenue of micro, small, and medium-sized enterprises (MSMEs), while considering cultural behavior as a moderating factor. Employing a quantitative research approach, the study utilizes Partial Least Squares (PLS) analysis to explore the relationships between the variables of interest. The population consists of various MSMEs, from which a representative sample is selected to ensure the findings are generalizable. PLS software is used for data analysis, facilitating accurate assessments of the validity and reliability of the constructs involved. The results reveal that all indicators related to the latent variables have P values less than 0.05, confirming their reliability and validity, with each indicator demonstrating a significant direct impact on revenue. Importantly, the study finds that cultural behavior moderates the relationship between accounting knowledge and revenue, highlighting the critical role of cultural factors in influencing financial outcomes. However, the research acknowledges certain limitations, such as potential biases in self-reported data and challenges in generalizing results across different cultural contexts. Future research could build on these findings by exploring additional moderating factors and employing longitudinal designs to gain deeper insights into the dynamics at play.